A checklist of Iranian Aderidae (Coleoptera: Tenebrionoidea) - Nardi, Gianluca; Ghahari, Hassan (Zootaxa, 2024)
The fauna of Iranian Aderidae (Coleoptera: Tenebrionoidea) includes five species within four genera, Aderus Stephens, 1829 (one species), Cobososia Collado & Alonso-Zarazaga, 1996 (two), Gompelia Alonso-Zarazaga, 2010 (one) and Phytobaenus R.F. Sahlberg, 1834 (one). Cobosia [sic!] (Franz 1987) is recognized as an incorrect subsequent spelling of Cobososia Báguena-Corella, 1962 (nomen nudum).